Layanan dan Pelayanan Perpustakaan : Menjawab Tantangan Era Teknologi Informasi - Himayah, Himayah (Jurnal Ilmu Perpustakaan & Informasi KHIZANAH AL-HIKMAH, 2013)
Nowadays, library services are varied compared several decades ago. Information technology gives a new meaning of the services provided by the library. There are several changes of the library usersâ orientation and expectation of what kind of information the need and want, and in what form. Also, they tend to rely on the internet to find up-to-date information, whereas it is difficult to provide by printed based material mostly provided by the libraries. And there is digital natives, a new generation of the library users, a generation that born with electronic devices in their hands. They may come the library not to look for books, but for free wi-fi.For user satisfaction, libraries should focus on the usersâ need, or user orientation. In the realization of the information orientation changing of the library users, the libraries should also change its policy, especially about library services, and collection development. Libraries not only about books, but also about information in any kind of forms and by any kind of meaning and technology. The users need technology based services and information, so that libraries should provide. By providing the usersâ need, libraries will not be abandoned by them and will be still the usersâ preference in seeking information and knowledge.